MIA HALL’S BEHAVIOUR CHANGE IN GAYLE FORMAN’S IF I STAY - Kusumaningrum, Kusumaningrum (LANTERN (Journal on English Language, Culture and Literature), 2016)
This final project analysis Gayle Forman’s novel entitled: If I Stay. The purpose of this final project is to analysis the behaviour change of the main character, Mia Hall. The study uses psychological approach and library research to analyse the behaviour change of the main character. Mia experiences three phases of behaviour change: unfreezing phase, movement phase and refreezing phase of Mia. Mia changes her behaviour and the social environment affect Mia’s behaviour change. Mia’s change is planned change. However, Mia decides not to change her behaviour permanently.